Competing interaction partners modulate the activity of Sgs1 helicase during DNA end resection. (7th June 2019) - Kasaciunaite, Kristina; Fettes, Fergus; Levikova, Maryna; Daldrop, Peter; Anand, Roopesh; Cejka, Petr; Seidel, Ralf
Abstract: DNA double‐strand break repair by homologous recombination employs long‐range resection of the 5′ DNA ends at the break points. In Saccharomyces cerevisiae, this process can be performed by the RecQ helicase Sgs1 and the helicase–nuclease Dna2. Though functional interplay between them has been shown, it remains unclear whether and how these proteins cooperate on the molecular level. Here, we resolved the dynamics of DNA unwinding by Sgs1 at the single‐molecule level and investigated Sgs1 regulation by Dna2, the single‐stranded DNA‐binding protein RPA, and the Top3‐Rmi1 complex. We found that Dna2 modulates the velocity of Sgs1, indicating that during end resection both proteins form a functional complex and couple their activities. Sgs1 drives DNA unwinding and feeds single‐stranded DNA to Dna2 for degradation. RPA was found to regulate the processivity and the affinity of Sgs1 to the DNA fork, while Top3‐Rmi1 modulated the velocity of Sgs1. We hypothesize that the differential regulation of Sgs1 activity by its protein partners is important to support diverse cellular functions of Sgs1 during the maintenance of genome stability. Synopsis: Homologous recombination repair of DNA breaks is initiated by DNA end resection, involving the budding yeast RecQ helicase Sgs1. A real‐time single‐molecule approach using magnetic tweezers reveals how this activity of Sgs1 is differentially controlled by its binding partners RPA, Dna2, and Top3‐Rmi1. DNA unwinding by Sgs1 is interrupted by strand‐switching events, as seen in other RecQ helicases. Sgs1‐mediated unwinding feeds single‐stranded DNA to Dna2 for degradation. RPA reduces the rate of Sgs1 translocation but increases processivity. Dna2 and Top3‐Rmi1 accelerate the rate of DNA unwinding by Sgs1. Abstract : Real‐time single‐molecule analyses of DNA unwinding activity of the S. cerevisiae RecQ helicase homolog uncover differential regulation of velocity, processivity, and affinity of Sgs1 through its binding partners Dna2, RPA, and Top3‐Rmi1.